2020
DOI: 10.1038/s41598-020-70625-7
|View full text |Cite
|
Sign up to set email alerts
|

The methylation status of the chemerin promoter region located from − 252 to + 258 bp regulates constitutive but not acute-phase cytokine-inducible chemerin expression levels

Abstract: Chemerin is a chemoattractant protein with adipokine properties encoded by the retinoic acid receptor responder 2 (RARRES2) gene. it has gained more attention in the past few years due to its multilevel impact on metabolism and immune responses. However, mechanisms controlling the constitutive and regulated expression of RARRES2 in a variety of cell types remain obscure. To our knowledge, this report is the first to show that DNA methylation plays an important role in the cell-specific expression of RARRES2 in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 62 publications
(83 reference statements)
0
21
0
Order By: Relevance
“…Aberrant promoter methylation is a hallmark of cancer, and was demonstrated to control constitutive chemerin expression in hepatocytes [32]. Maternal smoking during pregnancy was associated with reduced chemerin promoter methylation in the skin and induced gene expression [33].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant promoter methylation is a hallmark of cancer, and was demonstrated to control constitutive chemerin expression in hepatocytes [32]. Maternal smoking during pregnancy was associated with reduced chemerin promoter methylation in the skin and induced gene expression [33].…”
Section: Discussionmentioning
confidence: 99%
“…10,27,34−36 Chemerin expression is regulated by a variety of in ammatory and metabolic mediators in a manner dependent on cell type. 25,37 We previously showed that IL-1β and OSM upregulated chemerin expression in human skin cultures 7 , and mouse adipocytes 25 . Moreover, bacteria, like S. aureus, upregulate chemerin levels in models of human epidermis and mouse skin.…”
Section: Discussionmentioning
confidence: 98%
“…We have shown previously that acute-phase cytokines, interleukin 1b (IL-1β) and oncostatin M (OSM), regulate chemerin expression in mouse adipocytes and human 3D skin cultures. 7,25 Therefore, we next analyzed if these cytokines can affect the balance between newly discovered RARRES2 transcript variant 4 and others splice variants in mouse tissues. The transcript ratio remained stable in all investigated mouse tissues, and there were no statistically signi cant differences between PBS and cytokine treated animals (Fig.…”
Section: Expression Pattern Of Rarres2 Splice Variants Across Differementioning
confidence: 99%
See 2 more Smart Citations